THE CONSTRUCTION OF THE CHARACTER 'ANDRÉ VENTURA' IN THE PORTUGUESE PRESS: the politician’s profile in Revista E - Magalhães, Catarina (Brazilian journalism research, 2024)
ABSTRACT – Bearing in mind the narrative nature of journalism (Mesquita, 2003; Motta, 2013; Lits, 2015) and the potential to construct reality (Tuchman, 2002), the study focuses on one of the main categories of narrative (Reis, 2006, 2018). Therefore, we will analyze the character’s construction of ‘André Ventura’ in a particular journalistic genre: the profile. The goal is to unveil whether his figuration reflects and/or exacerbates characteristics of a populist leader, based on four categories of analysis: typification, discourse, characterization and lexicalization (Marques, 2016; Peixinho & Marques, 2016). The focus of the narrative was his career as a politician and the different procedures for characterizing the character demonstrate that the protagonist possesses and shares typical characteristics of a populist leader (Zúquete, 2022), such as aggressiveness and demarcation in relation to ‘corrupt elites’. The conclusions support the ambivalent role that journalism can play by covering politicians and populist phenomena. RESUMO – Partindo da natureza narrativa do jornalismo (Mesquita, 2003; Motta, 2013; Lits, 2015) e do potencial para construir a realidade (Tuchman, 2002), o estudo versa sobre uma das categorias centrais da narrativa (Reis, 2006, 2018). Assim, analisaremos a construção da personagem ‘André Ventura’ em um gênero jornalístico em particular: o perfil. O objetivo é desvendar se a sua figuração reflete e/ou exacerba características de um líder populista, partindo de quatro categorias de análise: tipificação, discurso, caracterização e lexicalização (Marques, 2016; Peixinho & Marques, 2016). O foco da narrativa foi o seu percurso como político e os diferentes procedimentos de caracterização da personagem, que demonstram que o protagonista possui e partilha características típicas de um líder populista (Zúquete, 2022), tais como a agressividade e a demarcação em relação às ‘elites corruptas’. As conclusões suportam o caráter ambivalente que o jornalismo pode desempenhar na cobertura de políticos e fenômenos populistas. RESUMEN – Partiendo del carácter narrativo del periodismo (Mesquita, 2003; Motta, 2013; Lits, 2015) y del potencial para construir la realidad (Tuchman, 2002), el estudio se centra en una de las categorías centrales de la narrativa (Reis, 2006, 2018). Por eso, analizaremos la construcción del personaje ‘André Ventura’ en un género periodístico particular: el perfil. El objetivo es develar si su figuración refleja y/o exacerba características de un líder populista, partiendo de cuatro categorías de análisis: tipificación, discurso, caracterización y lexicalización (Marques, 2016; Peixinho & Marques, 2016). El foco de la narrativa fue su carrera como político y los diferentes procedimientos para caracterizar al personaje demuestran que el protagonista posee y comparte características típicas de un líder populista (Zúquete, 2022), como la agresividad y la demarcación en relación con las ‘élites corruptas’. Las conclusiones respaldan la naturaleza ambivalente que puede desempeñar el periodismo al cubrir a políticos y fenómenos populistas.